Making Natural Acid-Base Indicators with a Science, Technology, Engineering, Mathematics (STEM) Approach to Chemistry Subjects During the Covid-19 Pandemic - Indah Agnestia, Meta (SEAQIS Journal of Science Education, 2023)
This study focuses on the implementation of the STEM approach in chemistry subjects to develop naturalacid-base indicators through contextual learning materials. The learning was conducted remotely using variousdigital services. To accomplish this, the experiment used the STEM approach with a Project-Based Learningmodel (STEM-PjBL), which was developed by Laboy-Rush and promoted by West Java Province EducationOffice in collaboration with SEAMEO QITEP in Science to develop natural acid-base indicators. The researchfindings were evaluated using qualitative descriptive methods to address the concerns that arose during thestudy. Data were collected through observations and student questionnaires regarding the implementation ofthe STEM approach in the acid-base indicator material. It was discovered that the STEM approach can beeffectively employed in online learning during the Covid-19 pandemic. This study utilised plant parts obtainedfrom the students’ surrounding environment. However, before this experiment, students’ knowledge about thenature of acid-base reactions in school snacks remain unknown.